###### Advertisements

###### Advertisements

**Solve the following equation for x, y ∈ R: **

(4 – 5i) x + (2 + 3i) y = 10 – 7i

###### Advertisements

#### Solution

(4 – 5i) x + (2 + 3i) y = 10 – 7i

∴ (4x + 2y) + (3y - 5x) i = 10 – 7i

Equating real and imaginary parts, we get

4x + 2y = 10

i.e., 2x + y = 5 ...(i)

and 3y – 5x = – 7 ...(ii)

Equation (i) x 3 – equation (ii) gives

11x = 22

∴ x = 2

Putting x = 2 in (i), we get

2(2) + y = 5

∴ y = 1

∴ x = 2 and y = 1.

#### APPEARS IN

#### RELATED QUESTIONS

Find the values of x and y which satisfy the following equations (x, y ∈ R): `(x + 1)/(1 + "i") + (y - 1)/(1 - "i")` = i

**Solve the following quadratic equation:**

8x^{2} + 2x + 1 = 0

**Solve the following quadratic equation: **

`2x^2 - sqrt(3) x + 1` = 0

**Solve the following quadratic equation: **

x^{2} – 4x + 13 = 0

**Solve the following quadratic equation: **

x^{2} + 3ix + 10 = 0

**Solve the following quadratic equation: **

2x^{2} + 3ix + 2 = 0

**Solve the following quadratic equation: **

x^{2} + 4ix – 4 = 0

**Solve the following quadratic equation: **

x^{2} – (5 – i)x + (18 + i) = 0

**Solve the following equation for x, y ∈ R: **

(1 – 3i) x + (2 + 5i) y = 7 + i

**Solve the following equation for x, y ∈ R: **

`(x + "i"y)/(2 + 3"i")` = 7 – i

**Solve the following equation for x, y ∈ R: **

2x + i^{9} y (2 + i) = x i^{7} + 10 i^{16}

**Solve the following quadratic equation.**

`8"x"^2 + 2"x" + 1 = 0`

**Solve the following quadratic equation.**

8x^{2} + 2x + 1 = 0

**Solve the following quadratic equation.**

8x^{2 }+ 2x + 1 = 0

**Solve the following quadratic equation.**

8x^{2} + 2x + 1 = 0

**Solve the following quadratic equation.**

8x^{2} + 2x + 1 = 0